Utilization of the litchi male-sterile line ‘MS1’—assisting in the selection of suitable harvesting periods for pollen donors for hybridization - Quan, Zhenxuan; Deng, Tianjie; Li, Yaoyao; Zheng, Xuewen; Wang, Yi; Li, Weicai (Frontiers in Plant Science, 2026)
Litchi (Litchi chinensis Sonn.), an important fruit originating in China, has received increasing attention for improving breeding efficiency in recent years due to the growing adoption of hybridization. It is a monoecious plant and predominantly relies on cross-pollination for seed production. Thus, enhancing pollen quality is essential for fruit set, which is closely associated with the developmental stages of male flowers. In this study, anthers of the litchi cv. ‘D13’ at five late developmental stages (half-exposed stage, fully-exposed stage, filament-elongated stage, anthesis, and browning stage) were investigated using paraffin sectioning, staining, in vitro germination, and controlled pollination techniques. Cytological characteristics of pollen were evaluated using paraffin sectioning, while pollen viability was assessed by I2-KI staining, and the germination rate was determined through in vitro culture on sucrose media. Furthermore, pollen collected from these five stages was used for controlled pollination of the male-sterile line ‘MS1’. The results indicated that pollen collected at the filament-elongated stage and anthesis exhibited higher viability and germination potential, which resulted in improved fruit set in the male-sterile line ‘MS1’. The study identified the filament-elongated stage and anthesis as optimal stages for pollen collection in litchi.